Pengaruh Project Based Learning An Minat Belajar Terhadap Hasil Belajar Menggambar Bentuk (Still Life) dalam Pelajaran Visual Art - Ardiansyah; Mustaji; Nurmida Catherine Sitompul (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
The research objectives are: (1) To examine the effect of the use of students' Project Based Learning (PjBL) learning models. (2) Test the influence of students’ learning interests. (3) Test the effect of the use of Project-Based Learning (PjBL) learning models with interest in learning towards learning outcomes in Drawing (Still life). This study used a pre-experiment design (Pretest - Posttest Control Group Design), by randomizing two groups (control group and experimental group). The results of the analysis in the study are as follows: 1) There is an influence of the use of the Project-Based Learning (PjBL) learning model on student learning outcomes in Drawing (Still life). 2) There is no influence of interest in learning on the results of learning to draw (Still life) students. 3) There are no interaction between Project Based Learning (PjBL) learning models and Direct learning models with the interest in learning towards students’ learning outcomes in Drawing (Still life).